Identifying factors affecting the weakening of entrepreneurship in graduates of Payam Noor universities in Tehran province - Alireza zare davijani; khadije Khanzadi; Abdolrahim Navehebrahim; Nader Soleimani (Institute of Management fekrenoandish, 2023)
AbstractThe aim of the current research is to identify the factors affecting the weakening of entrepreneurship in university graduates of Payam Noor universities in Tehran province. According to its purpose, the research method is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of implementation; of thematic analysis type, and exploratory in terms of the nature. The statistical population of the research in the qualitative part includes 11 experts in the field of entrepreneurship and management professors, selected by purposeful sampling. In the quantitative part, the statistical population of the research includes 3750 final year students. The sample size is 384 people based on Cochran's formula. Multi-stage cluster sampling (PPS) was used in this part. The data collection tool is a semi-structured interview (qualitative dimension) in the qualitative part; and in the quantitative part, the questionnaire is taken from the qualitative part. The analysis in the qualitative part is thematic analysis, and in the quantitative part it is confirmatory factor analysis using SPSS and PLS software. The output of the research is to emphasize the strengthening of four variables, including the individual and personal capabilities and qualifications of the graduates, strengthening the educational elements related to the development of entrepreneurship in the university, strengthening the government's support conditions (facilitation, support and encouragement), and finally intervention in the six environments effective on academic entrepreneurship. Extended abstractIntroductionAn integrated view of human resources in several discussions of higher education, employment, national development, transition from the concept of first and second generation universities and the tendency towards third generation universities and similar cases has caused the training of entrepreneurial personnel to be one of the basic tasks in leader educational institutions such as first-tier universities (Yazdan Panah & Zabeidi, 2017). Entrepreneurship education and academic entrepreneurship empowers human resources in a standard process and leads to an innovative business in the university or near the university, alone or with others. From the point of view of students, entrepreneurship is attractive due to the simultaneous response to three needs of affiliation, belonging, and success. Most students' life experiences have shown that the tendency towards academic entrepreneurship makes it easier to find a job and increase the efficiency and effectiveness of students, creating space for independent work experience and facilitating the process of realizing individual and organizational entrepreneurship (Grecu & Denes, 2017).Therefore, the researcher asked the main question: what are the factors affecting the weakening of entrepreneurship in university graduates of Payam Noor universities in Tehran province?Theoretical FrameworkThe entrepreneurial university and academic entrepreneurship in the new world has been removed from the emphasis of mere theory and are considered as one of the main drivers of social systems and the link between the university (technology and innovation systems), industry (production systems), and the government (the factor of creating development conditions) (Boruck Klein & Cesar Mafra, 2020). Based on this, the three concepts of entrepreneurship education, academic entrepreneurship and entrepreneurial university are considered as related concepts and generally having a longitudinal relationship with each other (Klucznik, 2021).Academic entrepreneurship depends on the entrepreneurial behavior of the members and active human resources in the university. Management studies show that identity development precedes behavioral actions and in order to realize academic entrepreneurship focused on students, it is necessary to strengthen their entrepreneurial identity in different ways as much as possible, and it is based on the level of behavioral expectations (Hayter et al, 2022).Mahmudi Khamiri Pur et al, (2022) investigated the identification of factors affecting the improvement of faculty members with an entrepreneurial approach (case study: Payam Noor University, Hormozgan Province). Based on the interviews conducted with experts in the field of human resources improvement, 71 basic themes along with 25 organizing themes were identified, and categorized based on the conclusion of the researcher in 5 comprehensive dimensions including the dimensions of individual improvement, organizational improvement, educational improvement, research improvement, and professional improvement.Karimpour Malekshah et al, (2022) investigated the identification of components and measuring the relationships of entrepreneurial knowledge dimensions in large-scale cooperatives. Based on the findings obtained from the research, the pattern of entrepreneurial knowledge formation in large-scale cooperatives has four dimensions: individual characteristics, infrastructure and organization, environment, and support. Also, in order to measure the effectiveness and affectability of the dimensions together, with the help of the Dimtel method, it was determined that the causes include individual characteristics, infrastructures, and the organization; and the effects include the environment and support.Research methodologyAccording to its purpose, the research method is applicable, and in terms of implementation, it is mixed (qualitative-quantitative), of thematic analysis type, and in terms of the nature, is exploratory type research. The statistical population of the research in the qualitative part is experts in the field of entrepreneurship and management professors, entrepreneurs who have more than 5 years of work experience and have relevant research activities in this field (project manager or main collaborator), and familiar with the structure and activity procedure of Payam Noor University (a previous student of the university, a lecturer at Payam Noor University, or have other meaningful and effective connections with this university). Sampling method in the qualitative dimension is targeted sampling; the research was conducted on the selected and introduced people as the statistical population, and eleven experts were selected as the research sample. In the quantitative part, the statistical population of this research includes final year students studying in 18 units and centers of Payam Noor in Tehran province in multiple disciplinary groups of humanities, basic sciences, technical and engineering; boys and girls separated, as well as graduates of the year of 1401 Payam Noor universities in the province. The number of qualified students is around 1750 and the number of graduating students is around 2000 (previous years). According to this rule, the total number of people in the statistical community under investigation is 3750 people. According to Cochran's formula, the sample size is equivalent to 384 questionnaires. Combined methods, semi-structured interview (qualitative dimension) and questionnaire survey of the target population and library studies (quantitative dimension) have been used collect information in this research.Research findingsThe analysis is thematic in the qualitative part, and confirmatory factor analysis in the quantitative part using SPSS and PLS software. The output of the research is to emphasize the strengthening of four variables, including the individual and personal capabilities and qualifications of the graduates, strengthening the educational elements related to the development of entrepreneurship in the university, strengthening the government's support conditions (facilitation, support and encouragement), and finally intervention in the six effective environments on academic entrepreneurship.ConclusionThe current research has been conducted with the aim of identifying factors affecting entrepreneurship among college graduates of Payam Noor universities in Tehran province. The result of this research is in agreement with the results of Mahmudi Khamiri Pur et al, (2022), Karimpour Malekshah et al, (2022), Daneshniya et al, (2021), Akbari et al, (2020), Dorri et al, (2020) ), Keshavarz (2014).